Scaled Agile Method Design: Case Study of a SaaS Company in Indonesia - Ramadhina, Farah Agia; Raharjo, Teguh (J-Icon : Jurnal Komputer dan Informatika, 2023)
Improving team coordination for optimal performance is one of the main challenges that organizations encounter when scaling their Agile practices. Therefore, numerous companies encounter difficulties in achieving their desired performance due to this challenge. This study aims to address the challenge by proposing a new project management method design for a Software as a Service (SaaS) company in Indonesia with ineffective project management, using a scaled Agile approach. This paper contributes to providing insight into the implementation of scaled Agile method design in an organization. The research follows qualitative methods based on the Design Science Research (DSR) methodology and the eight domains of the Project Management Body of Knowledge (PMBOK), comprising six phases and two iterations. The first iteration involves projecting the current state of the company's activities and resulting in a proposal for a new project management method. The second iteration involves developing and evaluating the proposed method against the PMBOK standard. According to the findings, there are two domains that align with PMBOK and project management in the firm, namely the Stakeholder and Cycle Performance Domains. Team Performance, Development Approach, and Life Planning Performance Domain, Project Work Performance Domain, Delivery Performance Domain, Measurement Performance Domain, and Uncertainty Performance Domain are the other domains that do not suit the standard. Adequate efficient training for team performance, fostering collaboration among team members building corporate culture, and aligning company business processes with Agile methods are essential to overcome some inconsistent results.